The Effect of SP/NK1R on the Expression and Activity of Catalase and Superoxide Dismutase in Glioblastoma Cancer Cells - Faranak Korfi; Hossein Javid; Reza Assaran Darban; Seyed Isaac Hashemy (Biochemistry Research International)
Introduction. Glioblastoma is the most malignant brain tumor with different therapeutic protocols, including surgery, radiotherapy, and chemotherapy. Substance P (SP), a peptide released by sensory nerves, increases cellular excitability by activating the neurokinin-1 receptor (NK1R) in several human tumor cells. Aprepitant is a potent and long-lasting NK1R antagonist, considered a new agent for inhibiting proliferation and induction of apoptosis in malignant cells. This study aimed to evaluate the effects of the SP/NK1R system on the expression and activity of catalase and superoxide dismutase (SOD) in the glioblastoma U87 cancer cell line. Methods. Cytotoxicity was measured by the resazurin test, 24 hours after treatment, with increasing aprepitant concentrations. The production of reactive oxygen species (ROS) was also measured 24 hours after treatment with SP and aprepitant. Enzymes activity of catalase and SOD was measured using the corresponding assay kits. Real-time PCR also measured their expression. Results. Aprepitant significantly reduced the viability of U87 cells in a concentration-dependent manner. ROS production was significantly reduced, and the activity of catalase and SOD increased after treatment with aprepitant. The expression of catalase and SOD enzymes also increased significantly in the presence of aprepitant. Conclusion. The present study showed that aprepitant inhibited SP’s oxidizing effects via inducing the antioxidant effects of catalase and SOD in the U87 cell line. Therefore, this drug might be introduced as a potential candidate for controlling glioblastoma cancer in animal models and clinical trials.